Millennial Street Food Consumption: An Integrated Theory of Reasoned Action Approach - Tobias-Mamina, Rejoice Jealous; Maziriri, Eugine Tafadzwa (International Review of Management and Marketing, 2023)
Street food vending is still prevalent in developing countries despite the enormous stride recorded in the areas of food processing. This study investigates the practicality of the extended theory of reasoned action for street-food patronage decisions. The framework is premised on six critical constructs- attitudes, subjective norm, past behaviour, Food safety concerns, patronage intention and actual patronage. Data were collected from 550 consumers in Gauteng to validate the integrated conceptual framework. Structural equation modelling (SEM) technique is used to analyse data relating to the hypothesised relationships in the model. The results indicated that subjective norms and food safety concerns positively and significantly influence patronage intention. Attitude towards street food and past behaviour negatively and insignificantly influenced patronage intention. Lastly, patronage intention had a positive and a significant influence on actual patronage. Drawing from the study’s findings, managerial implications are discussed, and limitations and future research directions are suggested. By and large, this study immensely contributes new knowledge to the existing body of consumer behaviour literature in Africa - a context that is often most neglected by some researchers in developing countries.